Adhesion of Candida Albicans and Candida Parapsilosis to Different Restorative Materials - Soley Arslan; Hacer Balkaya; Nazire Nurdan Çakır; Ayşe Nedret Koç; Burhanettin Avcı (Cumhuriyet University, 2019)
Objective: The aim of this study is to compare the susceptibility of seven different restorative materials (three conventional composite resins, two bulk-fill composite resins, one giomer, and one high viscosity glass ionomer material) to adhere Candida albicans and Candida parapsilosis.Material and methods: In this study, thirty cylindrical specimens of each material were made according to instructions of the manufacturers. The surface roughness of the specimens was assessed using a profilometer. Thereafter, the specimens were incubated with a reference strain of Candida albicans (ATCC 64548) and Candida parapsilosis (ATCC 22019). The proliferated colonies counted as CFU/ml. One-way analysis of variance (ANOVA) was used to evaluate the surface roughness and the adhesion value of the materials. Tukey's post-hoc test was used for subsequent pairwise comparisons.Results: There was a statistically significant difference between the groups in terms of the surface roughness of the materials (p<0.05). The high viscosity glass ionomer material exhibited significantly higher surface roughness values while X-trafil (a bulkfill composite resin) had the lowest surface roughness values. Also, there was a significant difference between Candida adhesion values of the materials (p<0.05). Conclusion: There was no significant relationship between surface roughness and adhesion of Candida albicans and Candida parapsilosis. Involvement was seen more for Candida albicans compared to Candida parapsilosis in all restorative materials.